1997
DOI: 10.1172/jci119737
|View full text |Cite
|
Sign up to set email alerts
|

Productive infection of dendritic cells by HIV-1 and their ability to capture virus are mediated through separate pathways.

Abstract: There is substantial evidence that dendritic cells (DC) residing within epithelial surfaces (e.g., Langerhans cells) are the initial cells infected with HIV after mucosal exposure to virus. To study DC-HIV interactions in detail, we propagated Langerhans cell-like DC from cord blood CD34 ϩ cells and from adult blood plastic-adherent PBMC in the presence of cytokines (GM-CSF, IL-4, and/or TNF-␣ ). DC pulsed overnight with HIV BaL or HIV IIIB were infected productively with both viral subtypes (as assessed by PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
165
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(173 citation statements)
references
References 47 publications
8
165
0
Order By: Relevance
“…We demonstrated that DCs but not M⌽s exhibit an extraordinary capacity to transmit virus to CD4 ϩ T cells, consistent with previous studies (16,17,28,74,75). In DC:T cell cocultures, viral production increased 1088-fold compared with that in DCs alone.…”
Section: Discussionsupporting
confidence: 91%
“…We demonstrated that DCs but not M⌽s exhibit an extraordinary capacity to transmit virus to CD4 ϩ T cells, consistent with previous studies (16,17,28,74,75). In DC:T cell cocultures, viral production increased 1088-fold compared with that in DCs alone.…”
Section: Discussionsupporting
confidence: 91%
“…Here, DC-SIGN efficiently transmits the virus to T lymphocytes, resulting in productive HIV infection of T cells (26). The mechanism of protection of the virus by DCs is currently unknown, but several studies have demonstrated intracellular localization of virions in DCs (27). This, together with the fact that the cytoplasmic tail of DC-SIGN contains internalization motifs, prompted us to analyze the intracellular routing of DC-SIGN upon binding of soluble ligand.…”
Section: The Dendritic Cell-specific Adhesion Receptor Dc-sign Internmentioning
confidence: 99%
“…Another important issue in the field of DC-HIV biology is that data derived from studies using particular subtypes of DC (e.g., Langerhans cells vs monocyte-derived DC, immature vs mature DC, myeloid vs plasmacytoid DC) have clearly demonstrated disparate results. Regarding the immunologic function of HIV-infected DC or of DC isolated from HIV-infected individuals, existing literature on this topic is also varied (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Some have claimed significant APC defects and others none.…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…As previously described (15,17,26), plastic-adherent PBMC from healthy adults were cultured for 1 wk in RPMI-based complete medium containing 10% heat-inactivated FBS (Biofluids, Rockville, MD), 1000 U/ml recombinant human GM-CSF (Immunex), and 1000 U/ml recombinant human IL-4 (R&D Systems, Minneapolis, MN). At day 7, DC were harvested, washed, and resuspended in a mixture containing the following mouse anti-human mAbs (each at 5 g/ml): anti-CD3, anti-CD14, anti-CD16, and anti-CD19.…”
Section: Preparation Of Cellsmentioning
confidence: 99%